Room Temperature Quantum Spin Hall Insulator in Ethynyl-Derivative Functionalized Stanene Films - Zhang, Run-wu (Sci Rep, 2016)
Quantum spin Hall (QSH) insulators feature edge states that topologically protected from backscattering. However, the major obstacles to application for QSH effect are the lack of suitable QSH insulators with a large bulk gap. Based on first-principles calculations, we predict a class of large-gap QSH insulators in ethynyl-derivative functionalized stanene (SnC(2)X; X = H, F, Cl, Br, I), allowing for viable applications at room temperature. Noticeably, the SnC(2)Cl, SnC(2)Br, and SnC(2)I are QSH insulators with a bulk gap of ~0.2 eV, while the SnC(2)H and SnC(2)F can be transformed into QSH insulator under the tensile strains. A single pair of topologically protected helical edge states is established for the edge of these systems with the Dirac point locating at the bulk gap, and their QSH states are confirmed with topological invariant Z(2) = 1. The films on BN substrate also maintain a nontrivial large-gap QSH effect, which harbors a Dirac cone lying within the band gap. These findings may shed new light in future design and fabrication of large-gap QSH insulators based on two-dimensional honeycomb lattices in spintronics.